Effects of Resource Limitations and Cost Influences on Computer Virus Epidemic Dynamics and Tipping Points - Chung-Yuan Huang; Chuen-Tsai Sun (Discrete Dynamics in Nature and Society)
One of the most important assessment indicators of computer virus infections is epidemic tipping point. Although many researchers have focused on the effects of scale-free network power-law connectivity distributions on computer virus epidemic dynamics and tipping points, few have comprehensively considered resource limitations and costs. Our goals for this paper are to show that (a) opposed to the current consensus, a significant epidemic tipping point does exist when resource limitations and costs are considered and (b) it is possible to control the spread of a computer virus in a scale-free network if resources are restricted and if costs associated with infection events are significantly increased.